Immunological Perspective: Helicobacter pylori Infection and Gastritis - Hang Yang; Bing Hu (Hindawi Limited, 2022)
Helicobacter pylori is a spiral-shaped gram-negative bacterium. Its infection is mainly transmitted via oral-oral and fecal-oral routes usually during early childhood. It can achieve persistent colonization by manipulating the host immune responses, which also causes mucosal damage and inflammation. H. pylori gastritis is an infectious disease and results in chronic gastritis of different severity in near all patients with infection. It may develop from acute/chronic inflammation, chronic atrophic gastritis, intestinal metaplasia, dysplasia, and intraepithelial neoplasia, eventually to gastric cancer. This review attempts to cover recent studies which provide important insights into how H. pylori causes chronic inflammation and what the characteristic is, which will immunologically explain H. pylori gastritis.